Beyond Gate Closure - Karsten Neuhoff; Sebastian Schwenen (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Current EU short-term market designs for electricity face several challenges in (i) securing efficient system operation (ii) unlocking the full potential of flexible resources and (iii) fostering effective use of transmission capacity. For a gradual reform of market design and to guarantee secure operation of (cross-border) flexible resources, firm nominations for generation and load are required already at intraday, with subsequent auctions taking network constraints into account. Alternatively, gate closure can be moved several hours ahead of real-time with SO administered balancing markets starting accordingly. In both cases all auctions subsequent to day-ahead trades could be based on complex bids and hosted at a common platform at TSO, ISO or PX, where also transmission capacity and capacity allocation is jointly calculated.
Keywords: Q41; Q42; Q48; L94; L95; 330; gate closure; electricity market design; gate closure; electricity market design